ANALISIS KEPUASAN DAN PREFERENSI KONSUMEN TERHADAP TEMPAT MAKAN AYAM GEPREK - Rachmat Wildan (Xplore: Journal of Statistics, 2018)
The culinary business is one of businessess that believed to be an economic business has better prospects. One of culinary business in Dramaga, Bogor, West Java which has very rapid development is ayam geprek, this is evidenced by the increasing number of similar culinary businesses are increasingly penetrated in the area. Based on the condition, one of the places to eat ayam geprek in Dramaga is Ayam Geprek Pejuang (AGP) assess is very important to know the level of interest and consumer satisfaction AGP and consumer preferences of ayam geprek. The method required to explain this case was conjoint method, Importance Performance Analysis (IPA) and Customer Statisfaction Index (CSI). The data was primary data by evaluating the combination of levels and attributes by rating. Based on the level of satisfaction and interest of respondents AGP was very satisfied with the attributes associated with AGP.